Experimeantal investigation of a pumped two-phase cooling system for densely packed electronic packages - Tan, Chin Siang. (2011)
This report carries out an experimental investigation on the heat transfer characteristics of a pumped two-phased cooling system which aims to cool high heat flux component. This investigation includes the enhancement heat transfer characteristics of the system by using of porous graphite foams of different levels of porosity along with low boiling point cooling fluids. Level of porosity of the graphite foams are set to be at 61% and 70% and coolants used are FC-72 and HFE7000. In this experimental study, the heat transfer coefficient with the use of 61% HTC POCOfoam and FC-72 is significantly higher than the rest of the combination. 75% POCOfoam is believed to have a lower surface are to volume ratio which results in insignificant effect when different coolants are used. FC-72 has higher boiling point as compared to HFE 7000, which is more suitable in this high heat flux system. Evaporator of the existing system is re-customized to have transparent side wall and top cover so as to visualize the effect of flow boiling and bubbles formation in the system. Rate of bubbles formation is dependent on the wall temperature and the size of bubbles depends on the flow rate of the cooling fluid.